How to Study Placenames - Robert Rennick (Names, 2005)
Abstract The following presents instructions on how to properly study placenames. Beginning by assembling a list of placenames one then must decide what they want to know about each name. A list of information that is desired for each placename is enumerated, ranging from the spelling to the historical circumstance of the naming. A classification system is then presented for the names on the basis of the names themselves rather than the purposes for naming. The classification system ranges from personal names to mistake names and underived names where no known derivations can be found. One has a plethora of local and national sources to consult in finding a place or feature name. These range from historical maps and the U.S. Postal Service to county records and local residents. By investigating these sources one avoids name sources that are simply widely respected local lore and not properly evaluated historical fact.